GLOBAL TRADE TENSIONS DUE TO MADE IN CHINA 2025: A CASE STUDY OF THE US–CHINA CONFLICT AND ITS IMPLICATIONS FOR DEVELOPING COUNTRIES - Septiana, Angelia; Anggraini, Marchella; Suliha, Suliha (PERCIPIENCE International Journal of Social, Administration, & Entrepreneurship, 2024)
China's Made in China 2025 (MIC 2025) policy, launched as an industrialization strategy to dominate the global technology sector, and its implications for trade tensions between China and the United States. Analyzing the United States' economic policy response to MIC 2025, as well as the impact of the trade conflict on global trade stability and developing countries. These tensions have caused supply chain disruptions, changes in global investment flows, and increased market uncertainty. Findings show that developing countries are in a strategic yet vulnerable position, with opportunities for industrial relocation but also risks of new economic dependencies. This study uses the theoretical framework of hegemonic stability, liberalism, and trade uncertainty to examine this conflict as part of the restructuring of the global economic order. The results emphasize the need for adaptive strategies, strengthening domestic competitiveness, and active participation in multilateral forums to reduce the negative impacts of global trade tensions.